A global study of heritage site ecology, proclivity & loyalty. (December 2015) - Datta, Pratim; Bigham, George; Zou, Zoe; Hill, Geoffrey
Abstract: This research investigates the interplay of heritage site ecology namely tangible, intangible and cultural ecologies, on tourist loyalty towards heritage sites. This research conceives of the heritage site as choice environment open to tourist interactions that allow tourists to form a belief function that impacts their sense of affect and subsequently drives their intentions of conative loyalty towards heritage sites. Given the nature of heritage site as accommodating prior knowledge about heritage, we forward the concept of heritage proclivity as moderating affect and loyalty. Based on survey data collected in the US, UK, Europe and China, this research finds overall support for the model with mixed results for heritage proclivity, surfacing disparities in attitudes and intentions of global tourists.